Pertimbangan Hukum Dalam Hak Asuh Anak Pasca Perceraian - Wicaksana, Dika Hikmah; Trasaenda, Resfa Klarita; Pramesti, Indira Yekti Widya; Sabrina, Amanda Feby; Insani, Gema Mutiara; Ramadhani, Dwi Aryanti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The study cases were selected based on their relevance and complexity in the context of legal considerations in post-divorce child custody. Decision Number —/Pdt.G/2023/PN Smn was chosen because it provides an in-depth understanding of the legal framework and factors considered in post-divorce child custody cases. This research will use a qualitative approach with a case study design. This approach was chosen to understand in depth the legal considerations used in determining child custody after divorce. Researchers will study legal documents such as court decisions, judge's considerations, and statutory regulations related to determining child custody after divorce. Post-divorce child custody can be a difficult and controversial issue, especially in cases involving an unexpected and disorganized divorce. In this research the author focuses on the context of legal considerations in post-divorce child custody in Decision Number —/Pdt.G/2023/PN Smn. This research uses a qualitative approach with a case study design. The research results show that court decisions can influence various aspects of children's lives, including economic stability, parenting patterns, and interactions with the social environment. Therefore, judges must consider all these aspects carefully and comprehensively to ensure that the decisions taken truly prioritize the best interests of the child.